Driving-Related Neuropsychological Performance in Stable COPD Patients - Foteini Karakontaki; Sofia-Antiopi Gennimata; Anastasios F. Palamidas; Theocharis Anagnostakos; Epaminondas N. Kosmas; Anastasios Stalikas; Charalambos Papageorgiou; Nikolaos G. Koulouris (Pulmonary Medicine)
Background. Cognitive deterioration may impair COPD patient’s ability to perform tasks like driving vehicles. We investigated: (a) whether subclinical neuropsychological deficits occur in stable COPD patients with mild hypoxemia (PaO2 > 55 mmHg), and (b) whether these deficits affect their driving performance. Methods. We recruited 35 stable COPD patients and 10 normal subjects matched for age, IQ, and level of education. All subjects underwent an attention/alertness battery of tests for assessing driving performance based on the Vienna Test System. Pulmonary function tests, arterial blood gases, and dyspnea severity were also recorded. Results. COPD patients performed significantly worse than normal subjects on tests suitable for evaluating driving ability. Therefore, many (22/35) COPD patients were classified as having inadequate driving ability (failure at least in one of the tests), whereas most (8/10) healthy individuals were classified as safe drivers (P=0.029). PaO2 and FEV1 were correlated with almost all neuropsychological tests. Conclusions. COPD patients should be warned of the potential danger and risk they face when they drive any kind of vehicle, even when they do not exhibit overt symptoms related to driving inability. This is due to the fact that stable COPD patients may manifest impaired information processing operations.